2017
DOI: 10.1364/oe.25.018990
|View full text |Cite
|
Sign up to set email alerts
|

LED power consumption in joint illumination and communication system

Abstract: This paper addresses the power penalty in an illumination LED caused by visible light communication (VLC). This study models the extra power consumption of the LED by taking into account the convex relation between the dissipated electrical power versus the LED current on one hand and the concave relation between the output luminous flux versus the current on the other hand. The ratio of the output luminous flux to input electrical power, which is known the LED luminous efficacy, is analyzed considering variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…We also acknowledge that duty cycling may not be easy to implement, if high light quality without any flicker is demanded. We showed in [14] that during periods of modulation, the light output slightly drops due to convexity and nonlinearities in light output vs current (e.g. droop).…”
Section: Duty Cycling In Aco/flip/pam-ofdm Vlcmentioning
confidence: 95%
See 1 more Smart Citation
“…We also acknowledge that duty cycling may not be easy to implement, if high light quality without any flicker is demanded. We showed in [14] that during periods of modulation, the light output slightly drops due to convexity and nonlinearities in light output vs current (e.g. droop).…”
Section: Duty Cycling In Aco/flip/pam-ofdm Vlcmentioning
confidence: 95%
“…If eye-safety is the prime limitation, optical power may be an appropriate comparison [5]. It has been revealed that modulating a constant illumination light level costs extra electrical power, while the time-average optical power remains constant [14]. As the power consumption in mobile devices is limited, the electrical power consumed in the LED or in the driver is more appropriate, while this was less commonly studied in literature and we will focus on this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Companies such as pureLifi© [ 124 ], Phillips-Signify© [ 125 ], or Oledcomm© [ 126 ] have already presented different commercial solutions. Its final implementation in the market continues suffering problems mainly due to the need to integrate receiving devices in commercial equipment, to the consumption associated with emitting lamps [ 127 , 128 , 129 ], and synchronization problems when several transmitters coincide in the same room, working in a cellular architecture [ 130 , 131 , 132 ]. This type of solution may be of great interest in a tourist facility as it allows offering high-density services (video streaming, video conferences, gaming systems, and augmented or virtual reality) without overloading conventional radio links and with enhanced security compared to traditional wireless links.…”
Section: Smart Services On Tourism Facilitiesmentioning
confidence: 99%
“…Light scattering effect is a phenomenon caused by SEPs when it is in the pcLEDs with conformal phosphor structure according to the Mie-scattering theory and will be calculated with the help of MATLAB [21][22][23][24][25]. The following equations are the instruments for calculating the scattering coefficient μsca(λ), the anisotropy factor g(λ), the decreased scattering coefficient δsca(λ) and the scattering amplitude functions S1(θ) and S2(θ):…”
Section: Analyzation On the Scattering Effectmentioning
confidence: 99%